Bundle branch block in cardiac arrest survivors without ischemic heart disease. (April 2023) - Holm, Julie Terp; Stampe, Niels Kjær; Bhardwaj, Priya; Jabbari, Reza; Gustafsson, Finn; Risum, Niels; Tfelt-Hansen, Jacob; Winkel, Bo Gregers
Abstract: Aims: Cardiac arrest (CA) survivors with left/right bundle branch block (LBBB/RBBB) and no ischemic heart disease (IHD) have not been previously characterized. The aim of this study was to describe heart failure, implantable cardioverter defibrillator (ICD) therapy and mortality in this population. Methods: Between 2009 and 2019 we consecutively identified all CA survivors with a consistent bundle branch block (BBB) defined as a QRS ≥ 120 ms, who had a secondary prophylactic ICD implanted. Patients with congenital and ischemic heart disease (IHD) were excluded. Results: Among 701 CA-survivors who survived to discharge and received an ICD, a total of 58 (8%) were free from IHD and had BBB; 46 (79%) had LBBB, 10 (17%) had RBBB and 2 (3%) had non-specific BBB (NSBBB). The prevalence of LBBB was 7%. Pre-arrest ECG were available in 34 (59%) patients; 20 patients (59%) had LBBB, 6 (18%) had RBBB, 2 (6%) had NSBBB, 1 had (3%) incomplete LBBB, and 4 (12%) without BBB. At discharge, patients with LBBB had a significantly lower left ventricular ejection fraction (LVEF) than patients with other types of BBB, p < 0.001. During follow-up, 7 (12%) died after a median of 3.6 years (IQR: 2.6–5.1) with no difference between BBB subtypes. Conclusion: We identified 58 CA-survivors with BBB and no IHD. The prevalence of LBBB among all CA-survivors was high, 7%. During CA hospitalization LBBB patients presented with a significantly lower LVEF than patients with other types of BBB (P < 0.001). ICD treatment and mortality did not differ between BBB subtypes during follow-up.